The Testing Palm Biodiesel and Transesterification Biodiesel from Waste Cooking Oil in Korlah-boat Engine in Real Conditions - Srichai, Prathan; Palasai, Wasan (Princess of Naradhiwas University Journal, 2019)
Variabilityof fuel prices in countries affectson fuel price instability. Diesel is also most a fuel that is affectedbyprice variability. The useof alternative energy fuels is an approachfor diesel engine. The large source of fuel energy production in Narathiwat province is palm oil that can be used to produce fuel. Due to lowerpalmoil prices, ithas a concept that using palm as an alternative fuel to reduce the demand on fossil fuels.Vegetable oil is one of the raw materials for cooking. After the vegetable oil expires, it will be the environmental pollution if it is dumped into the river and canal or improper disposal. Thisexpired vegetable oil can be used to produce biodiesel fuel.The effects of fuel pricesaffecton fishermen who fill in diesel engines to find fish.The use of palm biodiesel fuel and used vegetable oil reducesengine performance. Therefore, it is necessary to improve fuel physical properties by transesterification process. Variabilityof fuel prices in countries affectson fuel price instability. Diesel is also most a fuel that is affectedbyprice variability. The useof alternative energy fuels is an approachfor diesel engine. The large source of fuel energy production in Narathiwat province is palm oil that can be used to produce fuel. Due to lowerpalmoil prices, ithas a concept that using palm as an alternative fuel to reduce the demand on fossil fuels.Vegetable oil is one of the raw materials for cooking. After the vegetable oil expires, it will be the environmental pollution if it is dumped into the river and canal or improper disposal. Thisexpired vegetable oil can be used to produce biodiesel fuel.The effects of fuel pricesaffecton fishermen who fill in diesel engines to find fish.The use of palm biodiesel fuel and used vegetable oil reducesengine performance. Therefore, it is necessary to improve fuel physical properties by transesterification process. In this research, a test is used to evaluate the fuel consumption of a boat filled with biodiesel in actual conditions. From the experiment, it was found that fuel consumptions for palm biodiesel and used vegetable oil are higher than that of diesel due to the higher consumption density. As a result of the acceleration boat using used waste cooking oil and palm biodiesel is lower than that of diesel by 5.07 and 9.2 percent. Fuel consumptions of palm biodiesel ester and used vegetable oil are higher than that of 28 and 43%, respectively, at boat speed 7 knots.Due to high viscosity of biodiesel effect on spray phase change from liquid to vapor which effect on spray pattern reduce engine combustion efficiency.